The Implementation Of Inquiry-Based Learning For The Teaching Of English At SMA N 2 Klaten In 2016/2017 Academic Year - Mulia Dewi, Erlita; , Prof. Endang Fauziati, M.Hum (2017)
This research aims at describing and explaining the implementation of Inquiry Based Learning for the teaching of English at SMA N 2 Klaten in 2016/2017 academic year. The type of this research is descriptive qualitative research, especially naturalistic study. The method of collecting data in this research is interview, observation, and document. This study consist of component of teaching learning namely; teacher's roles, student's roles, classroom procedure, and classroom techniques. The reseracher found the results as follows; 1) English teacher had roles as planner, facilitator, manager, explainer, motivator, and controller. 2) student's roles were student as subject learning, student as object learning, the learner is monitor and evaluator of his or her own progress, the learner learn from the teacher, from the other student and other teaching sources, the learner is a tutor of other learner, and the learner is a member of a group and learns by interacting with other. 3) classroom procedure used observing, questioning, gathering information, associating, and communicating. 4) classroom techniques used in teaching English was identifying key words, oral repetition, reading aloud, reading comprehension, discussion, question-answer, discussion group, and role playing. The researcher concludes that English teacher at SMA N 2 Klaten were implemented Inquiry Based Learning.